Hyperglycemia Aggravates Diet-Induced Coronary Artery Disease and Myocardial Infarction in SR-B1-Knockout/ApoE-Hypomorphic Mice - Gonzalez, Leticia; MacDonald, Melissa E.; Deng, Yak D.; Trigatti, Bernardo L. (Frontiers in Physiology, 2018)
Diabetes is a risk factor for development of atherosclerotic cardiovascular disease. Animal model studies in mice revealed that hyperglycemia increases development of atherosclerosis in the aorta as well as myocardial fibrosis in surgical models of coronary artery ligation, however the impact of hyperglycemia on coronary artery atherosclerosis and subsequent heart disease is less clear. To investigate the effect of hyperglycemia on atherosclerosis and coronary heart disease, we used a mouse model of diet-induced coronary artery atherosclerosis and myocardial infarction, the high fat/high cholesterol diet-fed SR-B1 knockout/apoE-hypomorphic mouse. Hyperglycemia was induced in these mice by streptozotocin treatment. This increased high fat/high cholesterol diet-dependent atherosclerosis development (p=0.02) and necrotic core formation (p=0.0008) in atherosclerotic plaques in the aortic sinus but did not increase the extent of atherosclerosis in coronary arteries. However it did increase the extent of platelet accumulation in atherosclerotic coronary arteries (p=0.017). This was accompanied by increased myocardial fibrosis (p=0.005) and reduced survival (p=0.01) compared to control-treated, normoglycemic mice. These results demonstrate that streptozotocin-treatment exerted differential effects on the level of atherosclerosis in the aortic sinus and coronary arteries. These results also suggest that SR-B1-knockout/apoE-hypomorphic mice may be a useful non-surgical model of diabetic cardiomyopathy in the context of coronary artery atherothrombosis.